PENERAPAN ALGORITMA KLASIFIKASI NAÃVE BAYES UNTUK ANALISIS SENTIMEN TENTANG PEMINDAHAN IBU KOTA NEGARA - Abdul Halim Hasugian; Raissa Amanda Putri; Mulya Alfan Simatupang (Smart Education, 2024)
Abstract: The decision of the Government of the Republic of Indonesia regarding the relocation of the territory of the Indonesian state capital to the Nusantara Capital in North Penajam Pasir, East Kalimantan is certainly an interesting discussion. This is a new record in Indonesian history because it has never happened before, becoming one of the big news stories that has generated a lot of opinions or reactions from the public. Twitter is one of the social media that people use to express opinions. Various kinds of opinions, both positive and negatif, are expressed by Indonesian people through their Twitter social media accounts. The data was obtained by crawling techniques from social media Twitter with the keywords